Vote-Buying and Muslim Family Resilience in the Election Year: A Maqashid Review - Santoso, Lukman; Aisyah, Aisyah (Kartika: Jurnal Studi Keislaman, 2024)
Families have a central role in building resilience to political, socio-economic, and cultural challenges, including vote-buying practices that are detrimental and hinder the achievement of Sharia objectives. This article aims to explore the practice of money politics impacting the resilience of Muslim families in the political year from a maqashid perspective, especially in the practice of politics in Indonesia. Family resilience here does not only concern the family's problems in facing the challenges of life but is related to the maintenance of religion, soul, mind, property and offspring. This research shows that families with high religiosity awareness tend to be able to act as a filter against vote-buying practices by teaching moral values, including rejecting unethical practices in politics. However, rejecting this practice cannot be fully guaranteed because of other influencing factors, including social, economic and regional political factors. It is necessary to develop political patterns more orientated toward human welfare following the maqashid Sharia values. Strict law enforcement and political awareness in social development are also essential to reduce vote-buying practices and ensure the integrity of the democratic process. The family, as the smallest unit in society, has a significant impact on shaping consumer behavior and building family resilience by instilling religious values, especially in the context of Islam.